2020
DOI: 10.3390/diagnostics10030143
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of Droplet Digital PCR Over Real-Time Quantitative PCR for JAK2 V617F Allele Mutational Burden Assessment in Myeloproliferative Neoplasms: A Retrospective Study

Abstract: JAK2 V617F mutational status is an essential diagnostic index in myeloproliferative neoplasms (MPNs). Although widely used for detection of JAK2 V617F mutation in peripheral blood (PB), sensitive real-time quantitative PCR (qPCR) presents some methodological limitations. Recently, emerging alternative technologies, like digital droplet PCR (ddPCR), have been reported to overcome some of qPCR’s technical drawbacks. The purpose of this study was to compare the diagnostic utility of ddPCR to qPCR for JAK2 V617F d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…In the 99 samples analyzed by both techniques, there was an optimal correlation between QT-PCR and ddPCR, with the latest technique showing half a log higher sensitivity than the former one (5 × 10 −4 vs. 1 × 10 −3 ). PV and MF presented a similar median mutation burden (40.45%), higher than that observed in ET (21.35%) [ 125 ], differences that we also confirmed by different grades of the spleen stiffness observed by ultrasonography [ 126 , 127 , 128 ]. Finally, a Korean group compared a ddPCR assay for JAK2 V617F mutation with the results from pyrosequencing, once again showing the superiority of ddPCR [ 129 ].…”
Section: Ddpcr Applications In Hematologysupporting
confidence: 80%
“…In the 99 samples analyzed by both techniques, there was an optimal correlation between QT-PCR and ddPCR, with the latest technique showing half a log higher sensitivity than the former one (5 × 10 −4 vs. 1 × 10 −3 ). PV and MF presented a similar median mutation burden (40.45%), higher than that observed in ET (21.35%) [ 125 ], differences that we also confirmed by different grades of the spleen stiffness observed by ultrasonography [ 126 , 127 , 128 ]. Finally, a Korean group compared a ddPCR assay for JAK2 V617F mutation with the results from pyrosequencing, once again showing the superiority of ddPCR [ 129 ].…”
Section: Ddpcr Applications In Hematologysupporting
confidence: 80%
“…In PMF patients, there was a significant difference between positive and negative mutation individuals in terms of HCT% and Platelet Count. Examining these results with the results of other studies showed that the average of demographic and clinical variables in this study was higher than in other studies (34)(35)(36).…”
Section: Discussionsupporting
confidence: 65%
“…The excellent sensitivity and specificity of HPV detection using ddPCR in swabs without the need for invasive tissue biopsy have several potential applications for both diagnosis and disease surveillance. Furthermore, the ddPCR method is reported to be accurate, repeatable, reproducible ( 27 , 94 , 100 ), and cost-effective ( 23 , 25 , 26 , 90 ).…”
Section: Droplet Digital Polymerase Chain Reaction For Hpv Detectionmentioning
confidence: 99%
“…It has been demonstrated that ddPCR exhibits high sensitivity, accuracy, specificity, repeatability, and reproducibility compared to RT-PCR in quantifying HPV DNA ( 31 , 71 , 92 ), and therefore it can be used to test the self-sampled swabs. Since ddPCR method is reported to be accurate, repeatable, reproducible ( 27 , 94 , 100 ), and cost-effective ( 23 , 25 , 26 , 90 ), it is an ideal method for routine diagnostic testing.…”
Section: Droplet Digital Polymerase Chain Reaction For Hpv Detectionmentioning
confidence: 99%